1969
DOI: 10.1017/s0021932000023336
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive aspects of prejudice

Abstract: SummaryThe aim of this paper was to stress the importance of the adaptive cognitive functioning of man in the causation of prejudice. It was felt that this approach has the merits of economy, credibility and testability of explanation which are not always shared by views seeking the psychological causes of intergroup tensions in the evolutionary past of the species or in unconscious motivation. Three cognitive processes were considered from the point of view of their relevance to the genesis of prejudice in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
290
0
11

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(308 citation statements)
references
References 13 publications
7
290
0
11
Order By: Relevance
“…Hostile sexist beliefs in women's incompetence at agentic tasks characterize women as unfit to wield power over economic, legal, and political institutions, whereas benevolent sexism provides a comfortable rationalization for confining women to domestic roles. Similar ideologies (e.g., the "White man's burden") have been used in the past to justify colonialism and slavery (see Tajfel, 1969). Like hostile and benevolent sexism, these ideologies combine notions of the exploited group's lack of competence to exercise structural power with self-serving "benevolent" justifications ("We must bear the burden of taking care of them") that allow members of the dominant group to view their actions as not being exploitative.…”
Section: Sources Of Hostile and Benevolent Sexismmentioning
confidence: 96%
“…Hostile sexist beliefs in women's incompetence at agentic tasks characterize women as unfit to wield power over economic, legal, and political institutions, whereas benevolent sexism provides a comfortable rationalization for confining women to domestic roles. Similar ideologies (e.g., the "White man's burden") have been used in the past to justify colonialism and slavery (see Tajfel, 1969). Like hostile and benevolent sexism, these ideologies combine notions of the exploited group's lack of competence to exercise structural power with self-serving "benevolent" justifications ("We must bear the burden of taking care of them") that allow members of the dominant group to view their actions as not being exploitative.…”
Section: Sources Of Hostile and Benevolent Sexismmentioning
confidence: 96%
“…In a broad sense, a person's social or collective identities provide a sense of coherence and placement in society (Deaux, 1993;Roccas & Brewer, 2002;Tajfel, 1969). The groups to which a person belongs need not interact.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Second, superordinate identification contributes to the formation of a coherent selfconcept (Deaux, 1993;Tajfel, 1969), based on a consistent and explainable set of group memberships (e.g., human rights activists are unlikely to identify with the National Rifle Association). Researchers have explored individuals' identification with, and disidentification from, organisations with congruent or incongruent values to their own (Elsbach & Bhattacharya, 2001;Foster & Hyatt, 2007;Lock & Filo, 2012).…”
Section: Superordinate Identificationmentioning
confidence: 99%
“…Research has shown that individuals may accept or avoid certain social identities depending on their negative or positive cognitive representation of such identities (Ashmore, Deaux, & McLaughlin-Volpe, 2004;Arndt, Greenberg, Schimel, Pyszczinski, & Solomon, 2002;Mussweiler, Gabriel, & Bodenhausen, 2000;Tajfel, 1969). Thus, individuals are motivated to identify with groups that provide a sense of positive social identity (Abrams & Hogg, 1988).…”
Section: Age-group Dissociation In the Context Of Old Agementioning
confidence: 99%